Clinical manifestations and treatments of Protobothrops mucrosquamatus bite and associated factors for wound necrosis and subsequent debridement and finger or toe amputation surgery. (2nd January 2021) - Mao, Yan-Chiao; Liu, Po-Yu; Chiang, Liao-Chun; Lee, Chi-Hsin; Lai, Chih-Sheng; Lai, Kuo-Lung; Lin, Wen-Loung; Su, Hung-Yuan; Ho, Cheng-Hsuan; Doan, Uyen Vy; Maharani, Tri; Yang, Yi-Yuan; et al.
Abstract: Introduction: Protobothrops mucrosquamatus bite induces wound necrosis, coagulopathy, thrombocytopenia, rhabdomyolysis, and acute renal failure. The severity of the hematological derangements and associated factors for wound necrosis and subsequent surgery and the appropriate management of these conditions have not been well characterized. Although severe renal failure requiring hemodialysis has been reported following P . mucrosquamatus bite, the culprit snake may be erroneously classified. Materials and methods: A total of 186 patients with P . mucrosquamatus bites were retrospectively evaluated. They were categorized into group 1 (patients receiving debridement or finger/toe amputation) and group 2 (all other patients) to identify the associated factors for surgery. Characteristic data were compared between groups 1 and 2 and between definite and suspected cases. Results: No differences were observed between definite and suspected cases in terms of symptomatology and management. Of the 186 patients, 7 (3.8%) were asymptomatic, 179 (96.2%) experienced tissue swelling and pain, and 107 (57.5%) had local ecchymosis. Coagulopathy, thrombocytopenia, and renal impairment were found in 13 (7%), 19 (10.2%), and 7 (3.8%) patients, respectively. None of the patients required transfusion therapy or hemodialysis. Furthermore, no systemic bleeding or death occurred. Antivenom was administered to all 179 envenomed patients at a median of 1.5 h post-bite. The median total dose of the specific antivenom was 5.5 vials. In multivariate logistic regression analysis, finger as the bite site, bullae and blister formation, and wound infection were significantly associated with wound necrosis; whereas finger as the bite site and bullae and blister formation were related to debridement or finger/toe amputation. Discussion and conclusions: Protobothrops mucrosquamatus envenomation mainly exerts effects on local tissue. Systemic effects are uncommon and generally nonsevere and transient after the treatment with the specific antivenom. We speculated that severe renal failure requiring hemodialysis is not a typical finding of P . mucrosquamatus envenomation. Patients with finger as the bite site and bullae or blister formation should be carefully examined for wound necrosis, secondary infection, and subsequent surgery. Further evaluations of the efficacy of antivenom against local tissue effects and the effect of selective antibiotics in the management of bite wound infection are urgently required. Although the antivenom manufacturer suggested a skin test prior to use, we believed that it could be omitted because it does not accurately predict the allergic responses.